Mapping Moral Injury: Comparing Discourses of Moral Harm - Wiinikka-Lydon, Joseph (Oxford University Press, 2019)
Moral injury is a term whose popularity has grown in psychology and psychiatry, as well as philosophy, over the last several years. This presents challenges, because these fields use the term in different ways and draw their understanding from different sources, creating the potential for contradiction. This, however, is also an opportunity. Comparison between behavioral sciences and philosophy can help enrich understandings of harms considered not just psychological but moral. To this end, I provide an overview of the more influential writing of moral injury, mapping them into three broad discourses: clinical, juridical-critical, and structural. This overview then leads to a discussion of how comparative engagement among these discourses promises to expand on current theories of moral harm. I argue that such a comparison will demonstrate that more emphasis on structural violence will strengthen current understandings of moral injury, often understood in a more narrow sense to be a result of more direct, physical violence, allowing us to view moral injury as a result of institutional and social violence and injustices.
Mapping Moral Injury: Comparing Discourses of Moral Harm
Keywords: critical theory; moral injury; trauma; veteran; violence; morální zranění; trauma; veterán; násilí